A Comprehensive and Sustainable Recycling Process for Different Types of Blended End-of-Life Solar Panels: Leaching and Recovery of Valuable Base and Precious Metals and/or Elements - Kavousi, Maryam; Alamdari, Eskandar Keshavarz (Metals (Basel ), 2023)
The production of photovoltaic modules is increasing to reduce greenhouse gas emissions. However, this results in a significant amount of waste at the end of their lifespan. Therefore, recycling these solar panels is important for environmental and economic reasons. However, collecting and separating crystalline silicon, cadmium telluride, and copper–indium–gallium–selenide panels can be challenging, especially in underdeveloped countries. The innovation in this work is the development of a process to recycle all solar panel waste. The dissolution of all metals through the leaching process is studied as the main step of the flowchart. In the first step of leaching, 98% of silver can be recovered by 0.5 M nitric acid. Then, the second and third step involves the use of glycine for base metal dissolution, followed by the leaching of valuable metals with hydrochloric acid. The effect of parameters such as the initial pH, acid concentration, solid/liquid ratio, and hydrogen peroxide concentration is studied. The results show that up to 100% of Cu, Pb, Sn, Zn, Cd, In, Ga, and Se can be recovered under optimal conditions. The optimal conditions for the dissolution of Cu, Zn, and Cd were a glycine concentration of 0.5 M, a temperature of 25 °C, a solid/liquid ratio of 10 gr/L, and 1% of hydrogen peroxide. The optimized glycine concentration for the leaching of lead and tin was 1.5 M. Indium and gallium were recovered at 100% by the use of 5 M hydrochloric acid, S/L ratio = 10 gr/L, and T = 45 °C. Separation of selenium and tellurium occurred using 0.5 M HCl at a temperature of 60 °C. Additionally, for the first time, a general outlook for the recycling of various end-of-life solar panels is suggested.